2009
DOI: 10.1148/rg.292085078
|View full text |Cite
|
Sign up to set email alerts
|

Schatzker Classification of Tibial Plateau Fractures: Use of CT and MR Imaging Improves Assessment

Abstract: The Schatzker classification system for tibial plateau fractures is widely used by orthopedic surgeons to assess the initial injury, plan management, and predict prognosis. Many investigators have found that surgical plans based on plain radiographic findings were modified after preoperative computed tomography (CT) or magnetic resonance (MR) imaging. The Schatzker classification divides tibial plateau fractures into six types: lateral plateau fracture without depression (type I), lateral plateau fracture with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1
25

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(126 citation statements)
references
References 22 publications
2
98
1
25
Order By: Relevance
“…In agreement with Wicky et al (11) and Markhardt et al (12), whose studies confirmed that CT showed tibial plateau fractures more accurately and enabled greater precision of preoperative planning, there was no statistically significant change in relation to operative planning in the present study after viewing the CT.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with Wicky et al (11) and Markhardt et al (12), whose studies confirmed that CT showed tibial plateau fractures more accurately and enabled greater precision of preoperative planning, there was no statistically significant change in relation to operative planning in the present study after viewing the CT.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that a plain anteroposterior radiograph depicting a lateral plateau depression ]14 mm and/or a lateral plateau widening ]10 mm was associated with a significantly increased risk of meniscal injury in Schatzker type II tibial plateau fractures [6]. Many investigators have found that surgical plans based on plain radiographic findings were modified after preoperative computed tomography or magnetic resonance imaging [13,29]. Schatzker II fractures with depression or widening approaching 5 mm deserve heightened vigilance in diagnosing the soft tissue injuries [7].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of fracture is typically indirect and accompanied by axial loading, resulting in compression and angular forces that cause split or metaphyseal fractures [3]. In addition, meniscal lesions, medial and lateral collateral ligament injuries, and cruciate ligament injuries are reported with tibial plateau fractures, with rates of up to 60% [4] [5]. Vangness et al reported that 47% of tibial plateau fractures were accompanied by meniscal injuries [6].…”
Section: Introductionmentioning
confidence: 99%